2018
DOI: 10.3390/cells7120247
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Role of Matrix Metalloproteinases in Liver Injury and Regeneration after Sterile Acute Hepatic Failure

Abstract: Acetaminophen (APAP) poisoning is one of the leading causes of acute hepatic failure and liver transplantation is often the only lifesaving alternative. During the course of hepatocyte necrosis, an intense accumulation of neutrophils is often observed within the liver microenvironment. Despite the classic idea that neutrophil accumulation in tissues causes collateral tissue damage, there is a growing body of evidence showing that neutrophils can also orchestrate the resolution of inflammation. In this work, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
(29 reference statements)
2
18
0
Order By: Relevance
“…This is in agreement with published studies demonstrating that neutrophil depletion by injection of Ly6G antibody markedly reduces chronic-binge ethanol feeding-induced liver injury and liver transplantation ischemia-reperfusion injury [8,38,39]. However, there are studies identifying the dual role for neutrophils in acetaminophen-induced acute liver injury, with neutrophil-mediated injury amplification early on, but exerting protective effects during the repair phase as depletion of neutrophils increases liver damage [40,41]. Also neutrophils contribute to spontaneous resolution of liver inflammation and fibrosis via microRNA-223 in CCl 4 -induced chronic liver injury [41].…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with published studies demonstrating that neutrophil depletion by injection of Ly6G antibody markedly reduces chronic-binge ethanol feeding-induced liver injury and liver transplantation ischemia-reperfusion injury [8,38,39]. However, there are studies identifying the dual role for neutrophils in acetaminophen-induced acute liver injury, with neutrophil-mediated injury amplification early on, but exerting protective effects during the repair phase as depletion of neutrophils increases liver damage [40,41]. Also neutrophils contribute to spontaneous resolution of liver inflammation and fibrosis via microRNA-223 in CCl 4 -induced chronic liver injury [41].…”
Section: Discussionsupporting
confidence: 92%
“…In fact, a reliable gating strategy to differentially assess KCs and liver DCs is still under debate. 20 , 21 , 28 , 39 Importantly, an overt infiltration of neutrophils occurred at later time points (9 weeks), which was previously described as a key factor for enhanced collateral liver damage upon insults, 14 , 23 , 24 , 40 , 41 suggesting that such early alterations in these subpopulations may constitute a hallmark in the evolution from simple steatosis to steatohepatitis. However, it is reasonable to hypothesize that such overt neutrophil infiltration during NAFLD onset might also function as a backup strategy for bacterial clearance and phagocytosis while KCs are relatively absent.…”
Section: Discussionmentioning
confidence: 64%
“…Intravital imaging revealed that neutrophils contributed to healing by phagocytosing debris and promoting vascular regrowth in part by making new sleeves for blood vessels to grow into (69). Along the same lines, a recent study identified a dual role for neutrophils in acetaminophen-induced acute liver injury, with neutrophil-mediated injury amplification early on, but protective effects during the repair phase, as depletion increased liver damage (111). The early phase may reflect killing and/or removal of injured cells that presents as increased injury but is required for repair.…”
Section: Neutrophils In Tissue Repairmentioning
confidence: 95%